Эффективная система охлаждения квантоскопов - Lavrenchenko, G. K.; Khmelnyuk, M. G.; Savichev, V. P. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
A cascade compressor cooling system has been developed, implementing the Linde cycle with multicomponent working fluids, with an operating life of 30,000 hours. The implementation of the cycle based on lubricated hermetic single-stage compression compressors HKV-8, using efficient multicomponent working fluids, made it possible to reduce the mass from 100 to 30 kg and the dimensions of the cooling unit from 700×700×420 to 430×430×240 mm.